PROPAGATION OF LOCAL GRAPE VARIETIES BASED ON IN VITRO TECHNOLOGY (Scientific journal of the Fergana State University, 2023)
This article reviews the results of research on microclonal propagation of grape varieties in vitro. The study provides information on various nutrient media for microclonal reproduction of grape varieties, adaptation of in vitro grape seedlings to nosteril conditions, reproduction and preservation of original genotypes. As a result, the most optimal methods and nutrient medium for in vitro propagation of selected grape varieties were determined.